Association between the c.910A>G genetic variant of the XRCC1 gene and susceptibility to esophageal cancer in the Chinese Han population - Chen,X.Q. (2013)
Esophageal cancer (EC) is a common malignancy worldwide. The X-ray repair cross-complementing 1 gene (XRCC1) is one of the most important candidate genes for influencing susceptibility to EC. This study aimed to investigate the effect of XRCC1 genetic variants on susceptibility to EC. A total of 383 EC patients (males: 239, females: 144, mean age: 56.62) and 387 cancer-free controls (males: 251, females: 136, mean age: 58.23) were enrolled in this study. The c.910A>G genetic variant of theXRCC1 gene was determined by polymerase chain reaction-restriction fragment length polymorphism and DNA sequencing methods. The allele and genotype frequencies indicated statistical differences between EC patients and cancer-free controls. The c.910A>G genetic variant was statistically associated with increased susceptibility to EC [GGvs AA: odds ratio (OR)=1.79, 95% confidence interval (CI)=1.12-2.86, P=0.014; GG vs AG/AA: OR=1.76, 95%CI=1.13-2.75, P=0.013; G vs A: OR=1.25, 95%CI=1.01-1.55, P=0.041]. The allele G and genotype GG could contribute to the increased susceptibility to EC. Our findings suggest that the c.910A>G genetic variant is associated with susceptibility to EC in the Chinese Han population, and might be used as a molecular marker for detecting susceptibility to EC.